Disease Severity Based on Autologous Serum Skin Test Result in Chronic Spontaneous Urticaria Patients at Dermatology and Venereology Outpatient Clinic of Dr. Mohammad Hoesin General Hospital Palembang - Mahvira Chow Liana Herman Adil; Nopriyati; Desi Oktariana; Yuli Kurniawati; Gita Dwi Prasasty (RSUP Dr Moh Hoesin Palembang, 2021)
Studies on the severity of chronic spontaneous urticaria based on the results of theAutologous Serum Skin Test (ASST) have been done before, but the results vary so thereare still differences of opinion among some researchers. This study aims to determinethe correlation between disease severity and ASST results in chronic spontaneousurticaria patients at the Dermatology and Venereology (DV) Polyclinic of Dr. MohammadHoesin (RSMH) Palembang. The type of this study is analytic observational with cross-sectional design which used secondary data in the form of medical records. There were110 samples of chronic spontaneous urticaria patients at the DV clinic and it is 76samples that met the inclusion criteria. The highest distribution of chronicspontaneous urticaria patients was in the 17-25 year age group (23.7%) and the femalegroup (64.5%). The majority of chronic spontaneous urticaria patients had negativeASST results (52.6%) and mild disease activity (63.2%). Bivariate analysis showed nosignificant correlation between urticaria activity (UAS7 score) and ASST results with avalue of p = 0.287 or p > 0.05.